Gambaran Kejadian Shivering Pasca Spinal Anestesi Berdasarkan Karakteristik Suhu Tubuh Praanestesi dan Suhu Ruang Operasi pada Pasien Bedah Urologi di Rumah Sakit Islam Purwokerto - Niti Aliefviya Rosidi; Danang Tri Yudono; Amin Susanto (Lembaga Pengembangan Kinerja Dosen, 2025)
Shivering is a common side effect after spinal anesthesia that can increase oxygen demand, the risk of cardiac complications. This condition is triggered by factors such as body temperature, operating room temperature, and urological surgery-related factors like dehydration, bleeding, and the effects of anesthesia that disrupt thermoregulation, potentially leading to shivering. This study aimed to determine the incidence of shivering after spinal anesthesia based on pre-anesthetic body temperature and operating room temperature characteristics in patients undergoing urological surgery. A descriptive study with a cross-sectional approach was conducted on 41 urological surgery patients selected using quota sampling from a total population of 71 patients. The sample size was calculated using the Slovin formula. The results showed that most patients with pre-anesthetic hypothermia (<36.5°C) did not experience shivering (43.9%), and a similar finding was observed in patients with normal body temperature (36.5–37.5°C), where 24.4% did not experience shivering. Only one patient (2.4%) with hyperthermia experienced grade 2 shivering. In terms of operating room temperature, 63.4% of patients in rooms with temperatures below the ideal range (<18°C) and 4.9% in rooms with ideal temperatures (18–22°C) did not experience shivering. It can be concluded that the majority of patients in this study did not develop shivering after spinal anesthesia, however, 31.8% of them did experience shivering, which requires proper attention and early management. Further studies involving more diverse variables are recommended to explore additional factors that may contribute to the incidence of shivering.